Problems of broadcasting news programs - Melnik, G.; Kabylgazina, K.; Sultanbayeva, G. S.; Ashimova, A.; Akynbekova, A. B. (Farabi Journal of Social Sciences, 2020)
Today’s world is transformed into a single system that is entangled through informational links. Information space, which is associated with the emerging advanced technologies in the world significantly increased many times. The forms of social media are constantly increasing from Twitter to Facebook, to YouTube and TikTok. However, this abundance of choice does not negate the issues that arose from the earliest moments of broadcasting, namely – impartiality and objectivity. Kazakhstan centered right in the middle of Eurasian continent cannot stay away from the global changes. The process of modernizing the information space of our country is based on the historical and cultural characteristics of the people according to the national mentality and ethno-cultural linguistic state. During last decades, Kazakhstan underwent through massive information technology transformation that involved such as different filed as bureaucracy, financing, and broadcasting. In the ever-expanding media space traditional media outlets such as print, radio, and television are being perceived as “outdated” in comparison to social media tools that are able to present text, graphic and video images in single “package”. However, this abundance of choice does not negate the issues that arose from the earliest moments of broadcasting, namely – impartiality and objectivity. Key words: information, modernization, barriers, forms, modified social networks.